2010
DOI: 10.4141/cjss10019
|View full text |Cite
|
Sign up to set email alerts
|

Salinization of soil over saline-sodic overburden from the oil sands in Alberta

Abstract: S. 2010. Salinization of soil over saline-sodic overburden from the oil sands in Alberta. Can. J. Soil Sci. 90: 637Á647. Saline-sodic mine overburden (also referred to as spoil) removed to access the oil sands in the Athabasca region of Alberta is used as backfill in open pits and is also placed in large upland structures. These deposits are reclaimed with a soil cover to support re-vegetation. The chemistry within reconstructed soil profiles over saline-sodic overburden was investigated to determine the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…Rooting habits are adaptable to different soil conditions, but resource allocation to root responses represents additional stress on the tree (Gale and Grigal 1987). Since aspen had greater root length at intermediate soil depths, drought stress and any accompanying growth reductions are likely to be greater for aspen than for white spruce in soils in which salinity increases with depth, as they did at our study sites (Lilles et al 2010), and as they most likely will after oil sands reclamation (Kessler et al 2010).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Rooting habits are adaptable to different soil conditions, but resource allocation to root responses represents additional stress on the tree (Gale and Grigal 1987). Since aspen had greater root length at intermediate soil depths, drought stress and any accompanying growth reductions are likely to be greater for aspen than for white spruce in soils in which salinity increases with depth, as they did at our study sites (Lilles et al 2010), and as they most likely will after oil sands reclamation (Kessler et al 2010).…”
Section: Discussionmentioning
confidence: 53%
“…During reclamation of saline soils, nonsaline peat and peat mineral mixes are placed on top of saline-sodic overburden materials creating an environment where the highest salinity is encountered at depth and salinity may fluctuate over time (Kessler et al 2010). In both situations, assessing tree root response to variation in salinity with depth and assessing tree growth response over many decades are critical for understanding how forests develop on soils with salinity at depth.…”
mentioning
confidence: 99%
“…Kelly et al, 2009Kelly et al, , 2010, the concentration of ions measured within the snowpack in the Nikanotee Fen watershed were much lower than those measured in the water discharging through the slope run-off flumes. Salts can migrate into, and accumulate within, reclamation soil covers by diffusion from the underlying overburden material (Kessler et al, 2010). Kessler et al (2010) found that sulfate and sodium were the dominant anion and cation, respectively, within a reclamation soil cover layer.…”
Section: Discussionmentioning
confidence: 99%
“…Salts can migrate into, and accumulate within, reclamation soil covers by diffusion from the underlying overburden material (Kessler et al, 2010). Kessler et al (2010) found that sulfate and sodium were the dominant anion and cation, respectively, within a reclamation soil cover layer. Similarly, sulfate and sodium represented the highest two ion concentrations measured in the snowmelt run-off through the flumes in the current study, with average concentrations of 604.3 and 61.9 mg l À1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Surface strip mining for bitumen exposes marine sediments and shallow saline aquifers, resulting in salinization due to dumping of saline mine overburden, increased discharge of deep saline groundwater at the surface, and the disposal of saline waters used in the extraction of oil from the sands (Kessler et al 2010, Gibson et al 2013). These processes have been predicted to modify salinity regimes in boreal wetland ecosystems (Trites and Bayley 2009).…”
Section: Salinization Of Inland Wetlandsmentioning
confidence: 99%